Present status and future strategy of forage development in Nepal - Sharma, Bansi (Journal of Agriculture and Environment, 2015)
Livestock is an integral part of agricultural production system in Nepal. Animal feed have been one of the major production inputs drawing attention of the producers. There is excess green forage available during the monsoon period, but for the remaining six months, over the winter and spring, there is a lack of feed. In commercialized farming situations farmers compensate for shortages of forages with supplementation of expensive concentrate feeds. There are different cultivars of oats presently cultivated in Nepal. The winter crops oat is highly important to livestock raisers in Nepal. Oats are largely self-pollinated so farmers can save their own seed for several crops, provided that rogueing is carried out and the usual precautions are taken against mechanical contamination. Oat straw is good, palatable roughage and is also excellent bedding. With the introduction of multi-cut cultivars and new management technologies, the yield of fodder oats has gone up from 15-20 t/ha – 50-93 ha/ha. Non-legumes and legumes cropping can increase the condition of soil. So that farmers can be benefitted in subsequent cropping. Cost of production of livestock and its product can be lower down with better feeding practices of forage crops round the year.